Allopurinol and cardiovascular outcomes in patients with ischaemic heart disease: the ALL-HEART RCT and economic evaluation - Mackenzie, Isla S; Hawkey, Christopher J; Ford, Ian; Greenlaw, Nicola; Pigazzani, Filippo; Rogers, Amy; Struthers, Allan D; Begg, Alan G; Wei, Li; Avery, Anthony J; Taggar, Jaspal S; Walker, Andrew; et al. (Health technology assessment (Winchester, England), 2024)
Allopurinol is a xanthine oxidase inhibitor that lowers serum uric acid and is used to prevent acute gout flares in patients with gout. Observational and small interventional studies have suggested beneficial cardiovascular effects of allopurinol. To determine whether allopurinol improves major cardiovascular outcomes in patients with ischaemic heart disease. Prospective, randomised, open-label, blinded endpoint multicentre clinical trial. Four hundred and twenty-four UK primary care practices. Aged 60 years and over with ischaemic heart disease but no gout. Participants were randomised (1 : 1) using a central web-based randomisation system to receive allopurinol up to 600 mg daily that was added to usual care or to continue usual care. The primary outcome was the composite of non-fatal myocardial infarction, non-fatal stroke or cardiovascular death. Secondary outcomes were non-fatal myocardial infarction, non-fatal stroke, cardiovascular death, all-cause mortality, hospitalisation for heart failure, hospitalisation for acute coronary syndrome, coronary revascularisation, hospitalisation for acute coronary syndrome or coronary revascularisation, all cardiovascular hospitalisations, quality of life and cost-effectiveness. The hazard ratio (allopurinol vs. usual care) in a Cox proportional hazards model was assessed for superiority in a modified intention-to-treat analysis. From 7 February 2014 to 2 October 2017, 5937 participants were enrolled and randomised to the allopurinol arm ( = 2979) or the usual care arm ( = 2958). A total of 5721 randomised participants (2853 allopurinol; 2868 usual care) were included in the modified intention-to-treat analysis population (mean age 72.0 years; 75.5% male). There was no difference between the allopurinol and usual care arms in the primary endpoint, 314 (11.0%) participants in the allopurinol arm (2.47 events per 100 patient-years) and 325 (11.3%) in the usual care arm (2.37 events per 100 patient-years), hazard ratio 1.04 (95% confidence interval 0.89 to 1.21); = 0.65. Two hundred and eighty-eight (10.1%) participants in the allopurinol arm and 303 (10.6%) participants in the usual care arm died, hazard ratio 1.02 (95% confidence interval 0.87 to 1.20); = 0.77. The pre-specified health economic analysis plan was to perform a 'within trial' cost-utility analysis if there was no statistically significant difference in the primary endpoint, so NHS costs and quality-adjusted life-years were estimated over a 5-year period. The difference in costs between treatment arms was +£115 higher for allopurinol (95% confidence interval £17 to £210) with no difference in quality-adjusted life-years (95% confidence interval -0.061 to +0.060). We conclude that there is no evidence that allopurinol used in line with the study protocol is cost-effective. The results may not be generalisable to younger populations, other ethnic groups or patients with more acute ischaemic heart disease. One thousand six hundred and thirty-seven participants (57.4%) in the allopurinol arm withdrew from randomised treatment, but an on-treatment analysis gave similar results to the main analysis. The ALL-HEART study showed that treatment with allopurinol 600 mg daily did not improve cardiovascular outcomes compared to usual care in patients with ischaemic heart disease. We conclude that allopurinol should not be recommended for the secondary prevention of cardiovascular events in patients with ischaemic heart disease but no gout. The effects of allopurinol on cardiovascular outcomes in patients with ischaemic heart disease and co-existing hyperuricaemia or clinical gout could be explored in future studies. This trial is registered as EU Clinical Trials Register (EudraCT 2013-003559-39) and ISRCTN (ISRCTN 32017426). This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 11/36/41) and is published in full in ; Vol. 28, No. 18. See the NIHR Funding and Awards website for further award information.